Causal Modeling of Self Burden, Sosial Support, Spiritual Needs with CRF Using S3C-Latent - Putri Mentari Endraswari; Ridho Rahmadi; Christantie Effendy (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2020)
Cancer patients experience cancer-related fatigue (CRF) that are subjective and persistent. CRF can have a negative impact on psychosocial, spiritual, and self-perceived burden. To understand more deeply about CRF, we need to answer one fundamental question: how are the causal mechanisms (cause-effect) of the factors related to CRF. The studies related so far are still limited to correlation analysis between factors and have not focused on the mechanism of a causal relationship. The purpose of this study is to model the causal relationship between CRF and psychosocial, spiritual, and self-perceived burden, using a causal method called the Stable Specification Search for Cross-Sectional Data With Latent Variables (S3C-Latent). The results of this study are in the form of causal modeling between factors where self-burden has a causal relationship with CRF, spiritual need factors (religion) also have a causal relationship with CRF. Meanwhile, the social support factor (friends) with spiritual needs (religion) does not represent a causal relationship, but there is a strong association relationship. Meanwhile, the social support factor (friends) with CRF did not have a causal relationship or an association relationship between the two variables.